Wajah Toleransi Dan Perdamainan Dalam Kontestasi Historisitas - Abdullah Abdullah (UIN Sunan Gunung Djati Bandung, 2018)
The mission of Islamic teachings is to liberate human being from various forms of arrogance, arbitrariness and injustice whether committed by Muslims or non-Muslims, because Allah is God the Most Just who has infinite justice to His creatures throughout the universe. The diversity of religion, culture and civilization within the necessity of sunnatullah that must be maintained with the best possible, however there is no imbalance, misunderstanding and hostility among human being, whether in coreligionist or for another. In this case, I want to reveal the arguments of the Qur'an and Hadits and some of historical facts about the tolerance that tells begun when Islam came, which brought by Muhammad while his message was forwarded by the companions and the next generation. I will say that all of them must not be separated from the core of Islamic tolerance.This research belongs to a library research with a descriptive model that describes the beauty of tolerance and peace of Islamic teachings from time to time. Whereas in the hypothesis I found that tolerance is very important and should not be abandoned, especially concerning religious freedom, as it would be possible to abandon it then the damage in the plural society is inevitable, as some regions or countries that impose their will to embrace a particular religion, then they will certainly be destroyed by itself vis a vis to conserves tolerance it will experience its heyday, as it once was in Spain when Islam was in the peak of glory, then the Christian government suffered a period of decline for forcing their non-Christian citizens into Christianity and today, they are trying to catch up with trying to re-enforce tolerance.